Determination Decision Support System Using The School Fees Spp Simple Additive Weighting (SAW) - Puspita, Ika; Sitio, Arjon Samuel (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
School tuition fees are very influential on an educational institution, without the cost of school tuition fees experiences how an education agency Difficulties for students who can not afford. In making decisions 1 to Determine the cost of school tuition, especially in educational institutions. In educational institutions need to be supported by how much the school tuition fees will be paid. Educational institutions still Determine tuition fees manually. From the above problems, a decision support system (DSS) was made using the Simple Additive weighting method. Based on the calculation using the Simpe Additive weighting method for school tuition fees, the Reviews largest value is 2:55, 2.55so that alternatives A3, A5 are the alternatives to be chosen as alternatives entitled to pay school fees. Namely Citra Dewi,112 067.